ANALYSIS OF ERP SAP S/4HANA IMPLEMENTATION DESIGN TO IMPROVE PROCESS EFFICIENCY AND FINANCIAL REPORTING ACCURACY AT PT IAS - Zaini Widya Ramadhani; Fahmi Natigor Nasution; Meilita Tryana Sembiring (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2026)
PT IAS operates five business entities with four unintegrated ERP systems running in parallel — SAP ECC, SAP Business One, Acumatica, and Gamatechno. This condition has resulted in systemic inefficiencies, including a prolonged monthly financial close cycle, delayed group financial consolidation, manual intercompany reconciliation consuming 3–5 days per period, a data error rate of 2–5%, and 8–12 audit findings per year, with incomplete compliance with PSAK 110. This study aims to: (1) analyze the current state of PT IAS Group's financial reporting systems; (2) design an ERP SAP S/4HANA implementation to enhance process efficiency and reporting accuracy; (3) identify supporting factors and implementation challenges; and (4) develop an appropriate phased implementation roadmap. This study employs a qualitative descriptive approach using a case study method, with data collected through in-depth interviews, document analysis, and Root Cause Analysis (RCA) based on the Fishbone Diagram across five dimensions: People, Process, Technology, Data, and Governance. The findings indicate that SAP S/4HANA — encompassing the FI/CO, Group Reporting, MM, and SD modules, along with SAP BTP — is the optimal solution to address all identified gaps in the current state. The proposed implementation design is projected to reduce the monthly financial close to ≤3 working days (an 80% improvement), accelerate group consolidation to ≤2 days, improve reporting accuracy to ≥99.5%, and reduce audit findings to ≤2 per year. A three-year phased roadmap (2026–2028) is structured as follows: Phase 1: Finance Core (2026); Phase 2a: Source-to-Pay (2027); Phase 2b: Lead-to-Cash (2027); and Phase 2c: Technical & Governance (2027). The primary success factor is top management commitment and the IGH ecosystem, while critical risks — including poor master data quality and user resistance — are mitigated through a four-pillar change management strategy: People, Process, Technology, and Governance.